Viability of using a computer tablet to monitor an upper limb home exercise program in stroke. - Levy, Tamina; Killington, Maggie; Lannin, Natasha; Crotty, Maria (Physiotherapy Theory & Practice, 2021)
Aims: To evaluate the feasibility of using a tablet computer to monitor the amount of upper limb practice completed by stroke patients prescribed with a home program and to explore factors that influence adherence. Method: Ten consecutive participants randomized to the intervention arm of a randomized controlled trial investigating therapy after spasticity management for stroke patients (ACTRN 12615000616572) were recruited for this sub-study. Participants were asked to perform and record a prescribed 60-min upper limb program, based on the Graded Arm Supplementary Program, on a tablet computer daily. Four randomly selected recorded sessions for each participant were analyzed by the physiotherapist to assess adherence to the amount of exercise and content. Results: Mean score for the System Usability Scale was 85.5 (range 47.5–100) indicating that participants were accepting of the technology. Participants performed exercises on average for 50.32 min (range 26.42–68.37). Self-reported practice time was 59.44 min (range 48–67.5). Conclusion: Monitoring of patient practice using a tablet computer is feasible and may prove more reliable than self-report. There is variability in the amount of upper limb exercise stroke patients do at home.